India’s Joint Venture and Project Exports in Iran: An Analysis - Ahmad, Md. Firdos. (IJRDO - Journal of Business Management, 2016)
Keeping in mind the importance of joint venture and project export between two countries which resulted in exchange of technologies and capital, this aspect of the economic cooperation between India and Iran has analyzed in this paper. The planning era of both the countries started with the slogan of the reconstruction and diversification of the economy but find it difficult to go ahead while the existing restrictive rules and regulation and both counties liberalize their economies through the policies of New Economic Reforms. The first incidence about the joint venture between India and Iran came into figure in 1965 when Madras Refinery Ltd. was established. After that number of joint venture were made between these two countries over a period of time. Besides joint ventures India exported a number of consultancy services and projects since 1970s. At various Indian cooperative training institutions India provided training facilities to Iranians. The Iranian proposal was aimed at utilising the large quantities of natural gas in that country. Iran has largest reserves of natural gas in the world, can supply enough gas for re-export to Nepal, Bhutan, Bangladesh and other courties in the region. India and Iran decided to construct a natural gas pipeline that would run from Iran’s Qeshm Island to India.